Pengaruh Citra Merek dan Persepsi Harga terhadap Keputusan Pembelian Mie Gacoan - Siti Anisawati; Nursiah Fitri; Suriyadi Suriyadi; Dewi Comala Sari; Safaruddin Safaruddin (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
This quantitative research aims to answer questions about the influence of Brand Image and Price Perception on the Decision to Purchase Gacoan Noodles. Quantitative research methodology using survey methods. The sampling technique used the incidental technique with a sample size of 95 respondents. The data collection technique uses Multiple Linear Regression. The research results show that Brand Image has a partial influence on purchasing decisions for Gacoan Noodle Products. This is proven by the tcount value of 4.698 and a significance value of 0.000. Price perception partially influences purchasing decisions for Mie Gacoan products. This is proven by the t-count result of 8.971 and a significance value of 0.000. Meanwhile, based on the statistical calculation of Simultaneous tests on Purchasing Decisions, it can be concluded that Brand Image and Price Perception simultaneously influence Purchasing Decisions on Mie Gacoan products. This is proven by the Fcount of 63.885 and a significance value of 0.000. Based on the calculation of the Coefficient of Determination, it can be explained that the Ajasted R Square value is 0.572, which means that Purchase Decisions can be explained by the Brand Image and Price Perception variables of 58,1%, while 41,9% is explained by other variables not included in this research.